La relación entre moral y derecho en el paleopositivismo y el positivismo Jurídico - Jorge Guillermo Portela (Ius Humani. Jornal do direito, 2014)
In this paper, a historical chronicle of relations between morality and law´s done, as they have been conceived by legal positivists, since Austin´s developments until Hart´s propositions; most of them have been put forth since 1960, in the middle of XX Century. It is interesting note that, from a position that deny any possibility of a metaphysics, in which a value-neutrality was postulated, as it happened with Austin´s and Kelsen´s thesis, then was developed the idea that a link between morality and law is not only possible, but even necessary. The author has come to the conclusion that last Hart´s admission of a “soft” positivismo including a certain moral idea has made possible to obtain a stream of fresh air for the general theory of law and one contribution for the protection of the human rights. This has let a true advance in contemporary juridical ideas development.